Anatomy assessment of permanent mandibular premolar teeth in a selected Iranian population using cone-beam computed tomography - Seyed Mohsen Hasheminia; Mojdeh Mehdizadeh; Shervin Bagherieh (Wolters Kluwer Medknow Publications, 2021)
Background: Appropriate cleaning and shaping and three-dimensional obturation of the root canal system lead to a successful endodontic treatment. To achieve this, complete knowledge of the internal anatomy of root canals is necessary. Therefore, this study evaluated the number and shape of mandibular premolar roots and canals and classified their Vertucci classification using cone-beam computed tomography (CBCT) images of an Iranian sample population. Materials and Methods: This in vivo study was performed on CBCT images of patients aged 20-70 years who had attended a dental radiology center in Isfahan. CBCT images were examined in coronal, sagittal, and especially axial dimensions. Descriptive statistics were calculated. Groups were compared using the Chi-square of the Statistical Package for the Social Sciences. The level of significance was predetermined as 0.05. Results: In both first and second premolars, the most common classes were Type I followed by Type V. The Chi-square did not show significant differences between males and females in terms of Vertucci classes in the first (P = 0.305) or second premolar (P = 0.315). Conclusion: Since a thorough knowledge of root canal anatomy is necessary for successful root canal treatment and almost one out of ten mandibular premolars has additional canal in their root canal system, accurate evaluating of preoperative radiographs, taking CBCT images if necessary, and probing the root canal system with fine and precurved files should be done to negotiate the entire canal system.